(untitled) - McConnell, Campbell R. (New York, 2012)
McConnell, Brue, and Flynn’s Economics: Principles, Problems, and Policies is the #1 Principles of Economics textbook in the world. It continues to be innovative while teaching students in a clear, unbiased way
Keywords: Economic,Kinh tế